A MEMS-based measurement system for evaluating the force-length relationship of human induced pluripotent stem cell-derived cardiomyocytes adhered on a substrate. (19th March 2019) - Matsudaira, Kenei; Takahashi, Hidetoshi; Hirayama-Shoji, Kayoko; Nguyen, Thanh-Vinh; Tsukagoshi, Takuya; Shimoyama, Isao
Abstract: This paper reports on a method for evaluating the force-length relationship of adhering human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) on the substrate using a measurement system comprising of a micromachined movable plate and a piezoresistive force probe. The cells on the plate are stretched by pushing the movable plate with the piezoresistive cantilever, which is actuated by a piezo stage. The twitch forces and the applied stretch are measured quantitatively with the piezoresistive cantilever. The results demonstrated that the twitch forces of the hiPSC-CMs increased when a stretch was applied. This evaluation method improves the understanding of the intrinsic force-length relationship of hiPSC-CMs at the cellular scale.